Context-dependent responses to neighbours and strangers in wild European rabbits (Oryctolagus cuniculus). (Behavioural processes, 2014)
Territorial animals defend their territories against intruders. The level of aggression directed to intruders depends on the familiarity and/or the relative threat they pose, and it could be modified by the context of the interaction. We explored in a wild social mammal, the European rabbit (Oryctolagus cuniculus), whether residents responded more aggressively to strangers or to neighbours (dear enemy or nasty neighbour effects, respectively). We simulated the intrusion of neighbours or strangers in different parts of the territory of wild European rabbits in a suburban area in central Spain. For that, we placed faecal pellets of neighbouring or stranger rabbits in the territory of 5 rabbit colonies. Resident rabbits counter-marked preferably the odour stations with stranger odour, compared to the ones with neighbour odour, and they did not make a difference between neighbour and a non-odour control stimuli. The results suggest that rabbits show a dear enemy effect. However, repeated intrusions escalated the responses of rabbits towards neighbours. The location within the territory or the sex of the stranger did not affect the level of response. We conclude that in rabbits the relative threat posed by the intruder triggers the intensity of the interaction.